Hazardous Waste Generation and Composition from Electric Train Activities - Nabila Ardiana; I Wayan Koko Suryawan; Betanti Ridhosari; Mega Mutiara Sari (Universitas Islam Indonesia, 2022)
Transportation is one of the human needs in a big city like Jakarta. Currently, the implementation of public transportation is being scaled up to reduce vehicle emissions, especially those fueled by oil. One public transportation activity is electric trains that produce hazardous solid waste. This study aims to identify the generation and composition of hazardous waste from electric train transportation activities in Jakarta. This study uses quarterly secondary data from July 2019 to March 2020. The composition of hazardous waste is calculated based on the w/w weight ratio, then looks at the effect of time and phase of each time hazardous waste generation from electric train activities. The composition of the largest hazardous waste is contaminated packaging, scrap-contaminated, and contaminated waste is 28.14%; 23.34%; and 10.72%, respectively. The lowest hazardous waste generated is used lamps at 0.10%. Hazardous waste arises from activities that contaminate to produce hazardous or toxic properties. Based on the phase, solid hazardous waste is 96%, and liquid is 4%. The analysis of the variance test showed no significant difference in terms of time (sig. 0.679) and phase (sig. 0.534). Therefore, the data used show no difference in hazardous waste generated by time or phase.